RELATIONSHIP OF LEARNING INDEPENDENCE, PARENTING AND LEARNING ENVIRONMENT IN SCHOOLS WITH RESULTS OF MATHEMATICS STUDENTS IN SMP N 15 YOGYAKARTA - Rizka Nurcahyati; Suparyan Suparyan (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Low student learning outcomes are related to many factors. Learning Independence, Parenting Parents and the Learning Environment in Schools are several factors that are thought to be related to learning outcomes. This study aims to determine whether or not there is a positive and significant relationship between learning independence, parenting parents and the learning environment in schools with mathematics learning outcomes for students of class VIII SMP N 15 Yogyakarta odd semester 2016/2017 academic year. The population in this study were eighth-grade students of SMP N 15 Yogyakarta in the 2016/2017 school year, consisting of classes VIII F, VIII G, VIII H, VIII I, VIII J, with a total of 167 students. Samples were taken from class VIII H as a class of research samples with random sampling techniques to the class .. Data collection techniques using questionnaires to obtain data on learning independence, parenting parents and learning environment at school, as well as test methods to obtain data on mathematics learning outcomes. Research instrument test: validity test, different power test, and reliability test. Analysis prerequisite tests include normality test, linearity test, and independence test. Data analysis uses product moment analysis and multiple linear regression analysis. The results showed that there was a positive and significant relationship between learning independence, parenting parents, and the learning environment at school with mathematics learning outcomes for students of class VIII SMP N 15 Yogyakarta Odd Semester 2016/2017 Academic Year. This is indicated by Fcount Ftable is 451.4123 > 2.9223 with R = 0.9891 and R2 = 0.9783 with , with SR = , SR = and SR = 47.8309 , SE = , SE = and SE = .